Simulador de mensagens AFTN e OLDI - Recepção - Reis, Joaquim Tiago Valério Pacheco Veríssimo dos (2011)
An Air Traffic Management (ATM) system has the purpose of answering the needs for safety control and navigation. It is based on some technologies and procedures that are overlapped and correlated in order to create a dynamic and optimized system with several safety nets which increase its security by calling the attention of the Air Traffic Controller Operator (ATCO) and of other involved technicians for anomalous and potentially dangerous situations. NAV develops and constantly keeps in use one of these systems in the Flight Information Region (FIR) of Lisbon: the LISATM6 at control centre of Lisbon and TWRATM7 in the towers of mainland airports. Each one of these systems collects the data provided by several sources (Radars, adjacent FIR' s, CFMU8 among others) presenting it, after being processed, in a consistent and trustworthy way in order to be easily interpreted by ATCO’s, so that they can make traffic management decisions with total knowledge of the existing conditions in real time. LISATM and TWRATM are regularly subject to improvements and functionality additions which need to be tested and validated before being placed to operational use. For this test and validation phase, simulators are used to inject and collect data from the software to be tested in a test platform, without risking human and material resources. Beyond control based on information supplied by the radars, one of the main traffic management methods involves the anticipated knowledge of flight plans that supply information about the aircraft and its planned trajectory. When a flight involves more than one FIR there must exist information about that flight in all of them. It is also necessary that coordination between FIR takes place, as the time of the flight transfer from one FIR to another approaches. Nowadays, in order to test these situations there is no automatic mechanism capable of generating and validating flight plan information (AFTN9) and coordination (OLDI10) data exchange with ATM system. The present work aims at creating/implementing an additional functionality to the already existing simulator (SIMATM): to simulate the reception of Aeronautical Fixed Telecommunications Network (AFTN) and On-Line Data Interchange (OLDI) messages sent by LISATM, and the transmission of the respective response through a practical and functional Human Machine Interface (HMI). The main goal of this work is to observe, test and log AFTN and OLDI data sent by LISATM respectively to CFMU and ATM systems from adjacent FIR's. Additionally, it is also the intention to test and force anomalous behaviour in the responses given to the LISATM in its attempts of coordination with adjacent FIR’s (OLDI). Furthermore, this work aims to enter the domain of automated testing (of external interfaces mentioned above). This project will contribute with a new work tool for future projects, which will improve the level of security that NAV Portugal continuously promotes within the provided services.